THE EFFECT OF ADDING PUMPKIN FLOUR TO THE COLOR BRIGHTNESS AND GROWTH OF MOLLY FISH (Poecilia sphenops) - Jamal Mirdad Cibro; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from February 2019 to March 2019, for 30 days at the Aquaculture Technology Laboratory of the Faculty of Fisheries and Marine Sciences, Pekanbaru Riau University. The aims of study was to determine the effect of adding pumpkin flour to the brightness of the color of molly fish. The method used in this study was a laboratory-scale experimental method with a completely randomized design (CRD) design with four treatments given the treatment level of P0 = Takari feed, P1 = feed with 5% pumpkin flour, and P2 = feed with 10% flour pumpkinP3 = feed with 15% pumpkin flour. The best results were P3 treatment with feed with 15% yellow pumpkin flour, molly's body color 7.8 scor, absolute weight 1.04 grams and absolute length of 0.8 cm. Keywords: Pumpkin, Molly, feed.